Electrolyte and battery containing same

By using trifluoromethylsulfonate phenyl substituent and sulfur-based additives to form an interface film in the lithium-ion battery electrolyte, the problem of poor circulation performance of lithium-ion batteries at high voltage is solved, and a higher Kulun is achieved Efficiency and longer cycle life.

CN119170875AInactive Publication Date: 2024-12-20ZHEJIANG UNIV

Patent Information

Application Number
CN202411658084.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium-ion battery electrolyte cannot effectively suppress the positive electrode attenuation and electrolyte side reactions under high voltage conditions, resulting in poor circulation performance and stability.

Method used

An electrolyte containing functional additives with phenyl substituents of trifluoromethylsulfonate and sulfur-based additives is used to form a dense interface film, inhibit side reactions at the interface between the positive electrode and the negative electrode, and reduce the interface impedance.

Benefits of technology

It significantly improves the cycle life and Coulomb efficiency of lithium-ion batteries at high voltages, reduces the consumption of electrolyte and the damage to the positive electrode structure, and improves the cycle performance and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170875A_ABST
    Figure CN119170875A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte and a battery containing the electrolyte, and belongs to the technical field of electrolytes for batteries. Comprising electrolyte salt, an organic solvent and a functional additive, the mass percent of the functional additive in the electrolyte is 0.1-3%, and the functional additive structurally contains phenyl substituent of trifluoromethanesulfonate. When the electrolyte is applied to a sodium battery or a lithium battery, the battery can be endowed with relatively low interface impedance, good cycle efficiency and high coulombic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an electrolyte and a battery containing the electrolyte, belonging to the technical field of battery electrolytes. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, high operating voltage and long cycle life, and have received extensive attention and application in the fields of 3C digital products, power tools and energy storage. However, with the continuous increase in market demand, the requirements for the energy density of lithium-ion batteries are constantly increasing, which has prompted people to urgently develop high-energy-density lithium-ion batteries. The application of high-voltage positive electrode materials is the most effective way to increase the energy density of lithium-ion batteries.

[0003] At present, the electrolyte of commercial lithium-ion batteries is composed of lithium hexafluorophosphate (LiPF6) and carbonate solvents, which will undergo severe oxidative decomposition when exceeding 4.3V. Therefore, in order to improve the performance of lithium-ion batteries under high voltage conditions, more new high-voltage additives need to be developed in the hope of forming a good electrode-electrolyte interface and inhibiting the side reactions of the electrolyte and the positive and negative electrode materials, so as to better achieve the cycle stability of the battery under high voltage and realize the commercialization of high-energy density batteries. However, the commonly used electrolyte additives are only for negative electrode film formation, and the generated interface film is not dense and strong enough, which not only cannot effectively inhibit the attenuation of the high-voltage positive electrode and the side reactions of the electrolyte, but also leads to an increase in the interface impedance and deterioration of the cycle performance of lithium-ion batteries. Summary of the invention

[0004] In view of this, the present application first provides an electrolyte that can form a stable interface film on the surface of the positive electrode, inhibit the attenuation of the positive electrode, and improve the cycle life of the corresponding battery under high voltage.

[0005] Specifically, the present application is implemented through the following scheme: An electrolyte comprises an electrolyte salt, an organic solvent and a functional additive, wherein the mass percentage of the functional additive in the electrolyte is 0.1-3%, and the structure of the functional additive contains a phenyl substituent of trifluoromethyl sulfonate, and the structural formula thereof satisfies: R1 to R5 are each independently selected from a hydrogen atom, a substituted or unsubstituted C 1~10 Any of an alkyl group, a fluorine atom, a trifluoromethyl group, a trimethylsilyl group, and a cyano group.

[0006] Further, as a preference: The substituted or unsubstituted C 1~10 In the alkyl group, the substituent is a halogen.

[0007] The functional additive is any one of the following structures:

[0008] The electrolyte salt is a lithium salt or a sodium salt, and the concentration is 0.1 to 3.0 mol / L. More preferably, the electrolyte is a lithium salt, and the lithium salt includes but is not limited to lithium tetrafluoroborate, lithium hexafluorophosphate, lithium nitrate, lithium difluorooxalate borate, bisoxalate boric acid, lithium bisdifluorosulfonyl imide, lithium perchlorate, lithium bistrifluoromethylsulfonyl imide, etc., and can be one or more of them. When it is a combination of multiple substances, the present application has no special restrictions on the content of each specific substance. In some specific implementations, the electrolyte is preferably lithium hexafluorophosphate. The electrolyte salt concentration is preferably 0.5 to 2.5 mol / L, more preferably 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, or 3 mol / L.

[0009] The organic solvent is a mixture of one or both of carbonate and carboxylate. Carbonate includes but is not limited to the following fluorine-substituted or unsubstituted solvents: one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC); carboxylate includes but is not limited to the following fluorine-substituted or unsubstituted solvents: one or more of propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, propyl propionate, ethyl propionate, methyl butyrate, and ethyl butyrate. More preferably, the organic solvent is EC, EMC, and DEC. At this time, the mass ratio of EC, EMC, and DEC is preferably 1:1:1.

[0010] The mass percentage of the functional additive in the electrolyte is 0.1wt%~3wt%, preferably 0.1wt%, 0.5wt%, 1wt%, 2wt% and 3wt%. When the amount of the functional additive added is higher than 3wt%, the improvement effect on the battery cycle performance becomes worse; when the amount of the functional additive added is lower than 0.1wt%, the improvement effect is not obvious, so it is better to control the amount of the functional additive added to 1~3%.

[0011] The electrolyte in the above scheme also includes a sulfur additive, and the mass percentage y of the sulfur additive in the electrolyte and the mass percentage x of the functional additive in the electrolyte satisfy: 0.1%≤x+y≤5%, y≥0, and when the value is 0, it means that no sulfur additive is added. The mass percentage content of the sulfur additive in the electrolyte is 0~4.9wt%. More preferably, the sulfur additive is selected from at least one of vinyl sulfate (DTD), 1,3-propane sultone (PS), propenyl-1,3-sultone (PES), ethylene sulfite (ES), 4-propyl vinyl sulfate (PDTD), methylene disulfonate (MMDS), and methyl vinyl sulfone (MVS). The x+y is 1%, 2%, 3%, 4% or 5%. More preferably, the mass percentage y of the sulfur additive in the electrolyte and the mass percentage x of the functional additive in the electrolyte satisfy: 1%≤x+y≤4%.

[0012] The present application adds a phenyl-substituted functional additive containing trifluoromethyl sulfonate to the electrolyte, which can form a dense positive electrode electrolyte interface film (CEI) on the surface of the high-voltage positive electrode, inhibit the side reaction of the electrolyte at the positive electrode interface, reduce the consumption, decomposition and damage to the positive electrode structure of the electrolyte during the battery cycle, thereby improving the battery's cycle performance and coulomb efficiency. When a sulfur-based additive is added, the sulfur-based additive can be electrochemically reduced on the surface of the negative electrode to form a solid solid electrolyte interface (SEI), inhibiting the electrolyte side reaction at the negative electrode interface, and the interface film is rich in sulfur, which is also conducive to reducing the interface impedance. In particular, when the electrolyte satisfies 0.1≤x+y≤5, a thin and dense interface film can be formed on the positive and negative electrode surfaces at the same time, reducing the interface impedance, effectively improving the battery's cycle stability, and increasing the coulomb efficiency and cycle life; when x+y>5, the interface film formed on the positive electrode surface is too thick, resulting in excessive battery impedance, affecting the transmission of lithium ions, and then affecting the battery's cycle performance.

[0013] The second purpose of the applicant is to provide a battery, which includes a positive electrode, a negative electrode, a separator arranged between the positive electrode and the negative electrode, and the above-mentioned electrolyte, wherein the functional additives in the electrolyte form a film at the positive electrode to inhibit side reactions of the electrolyte at the positive electrode interface.

[0014] in: The electrolyte contains a sulfur additive, which forms a film on the negative electrode to inhibit the side reaction of the electrolyte at the negative electrode interface. At this time, the functional additive containing a phenyl-substituted trifluoromethylsulfonate and the sulfur additive are used in combination to protect the positive and negative electrode interfaces at the same time.

[0015] The positive electrode includes a positive electrode current collector and a positive electrode active material layer coated on the positive electrode current collector. In some specific implementations, the positive electrode current collector is a metal foil, including but not limited to aluminum foil, nickel foil, stainless steel, etc. For example, the positive electrode current collector can be aluminum foil. A positive electrode active material layer is arranged on the surface of the positive electrode current collector, which includes a conductive agent, a binder and a positive electrode active material. The mass ratio of the positive electrode active material, the conductive agent and the binder is 70~99.8:0.1~15:0.1~15, preferably 75~95:1~10:1~10, and more preferably 80~90:2~8:2~8. In some specific implementations, the positive electrode active material includes but is not limited to lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium iron phosphate (LiFePO4), ternary materials, LiNi x Co y Mn 1-x-y The conductive agent includes, but is not limited to, conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotube, etc. The binder includes, but is not limited to, one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid, polyamide, lithium polyacrylate, methacrylate, sodium polymethylcellulose, aluminum dihydrogen phosphate, etc.

[0016] The positive electrode material, conductive agent and binder are mixed evenly in a proper amount of solvent, such as N-methylpyrrolidone (NMP), and then coated on the positive electrode current collector. After drying, the positive electrode can be obtained. After drying, conventional processing steps such as rolling and slicing can also be included.

[0017] The negative electrode includes a negative electrode current collector and a negative electrode active material layer coated on the negative electrode current collector. The negative electrode current collector may be a metal foil, including but not limited to copper foil, nickel foil, stainless steel, etc. For example, the negative electrode current collector may be a copper foil. A negative electrode active material layer is provided on the surface of the negative electrode current collector, which includes a negative electrode active material, an optional conductive agent, and an optional binder. The mass ratio of the negative electrode active material, the conductive agent, and the binder is 70~99.8:0.1~15:0.1~15, preferably 75~95:1~10:1~10, and more preferably 80~95:2~8:1~5. The negative electrode active material of the negative electrode is selected from at least one of mesophase carbon microbeads, artificial graphite, natural graphite, and hard carbon. Conductive agents include but are not limited to one or more of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, etc. The binder includes, but is not limited to, one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC-Na), polyacrylic acid (PAA), polytetrafluoroethylene (PTFE), polyimide (PI), and the like.

[0018] After the negative electrode active agent, conductive agent and binder are mixed evenly in a solvent such as deionized water, the mixture is coated on the negative electrode current collector and dried to obtain the negative electrode. Conventional processing steps such as rolling and slicing may also be included after drying.

[0019] The diaphragm includes but is not limited to glass fiber microporous membrane, polyester microporous membrane, polyethylene microporous membrane, polypropylene microporous membrane, polytetrafluoroethylene microporous, ceramic coated diaphragm and the like.

[0020] In the battery structure provided by the present application, the functional additive containing phenyl substitution of trifluoromethyl sulfonate added to the electrolyte can reduce the interfacial impedance, inhibit the side reaction of the electrolyte at the interface of the positive and negative electrodes, significantly improve the stability of the electrolyte and electrode interface, reduce the consumption and decomposition of the electrolyte and the damage to the positive electrode structure during the battery cycle, thereby improving the battery's cycle performance and coulombic efficiency with low interfacial impedance, good cycle efficiency and high coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0022] Figure 1 (a) is a cycle life curve of the electrolyte prepared in Example 1 in a Gr / LCO button cell. Figure 1 (b) is a charge-discharge curve of the electrolyte prepared in Example 1 in a Gr / LCO button cell; Figure 2 (a) is a cycle life curve of the electrolyte prepared in Example 2 in a Gr / LCO button cell. Figure 2 (b) is a charge-discharge curve of the electrolyte prepared in Example 2 in a Gr / LCO button cell; Figure 3 (a) is a cycle life curve of the electrolyte prepared in Example 3 in a Gr / LCO button cell. Figure 3 (b) is a charge and discharge curve of the electrolyte prepared in Example 3 in a Gr / LCO button cell; Figure 4 (a) is a cycle life curve of the electrolyte prepared in Example 4 in a Gr / LCO button cell. Figure 4 (b) is a charge and discharge curve of the electrolyte prepared in Example 4 in a Gr / LCO button cell; Figure 5(a) is a cycle life curve of the electrolyte prepared in Example 5 in a Gr / LCO button cell. Figure 5 (b) is a charge-discharge curve of the electrolyte prepared in Example 5 in a Gr / LCO button cell; Figure 6 (a) is a cycle life curve of the electrolyte prepared in Example 6 in a Gr / LCO button cell. Figure 6 (b) is a charge-discharge curve of the electrolyte prepared in Example 6 in a Gr / LCO button cell; Figure 7 (a) is a cycle life curve of the electrolyte prepared in Example 7 in a Gr / LCO button cell. Figure 7 (b) is a charge-discharge curve of the electrolyte prepared in Example 7 in a Gr / LCO button cell; Figure 8 (a) is a cycle life curve of the electrolyte prepared in Example 8 in a Gr / LCO button cell. Figure 8 (b) is a charge-discharge curve of the electrolyte prepared in Example 8 in a Gr / LCO button cell; Fig. 9 (a) is a cycle life curve of the electrolyte prepared in Comparative Example 1 in a Gr / LCO button cell. Fig. 9 (b) is a charge and discharge curve of the electrolyte prepared in Comparative Example 1 in a Gr / LCO button cell; Fig.10 (a) is a cycle life curve of the electrolyte prepared in Comparative Example 2 in a Gr / LCO button cell. Fig.10 (b) is a charge and discharge curve of the electrolyte prepared in Comparative Example 2 in a Gr / LCO button cell; Fig.11 (a) is a cycle life curve of the electrolyte prepared in comparative example 3 in a Gr / LCO button cell. Fig.11 (b) is a charge-discharge curve of the electrolyte prepared in Comparative Example 3 in a Gr / LCO button cell; Fig.12 (a) is a cycle life curve of the electrolyte prepared in Comparative Example 4 in a Gr / LCO button cell. Fig.12 (b) is a charge-discharge curve of the electrolyte prepared in Comparative Example 4 in a Gr / LCO button cell; Fig.13 (a) is a cycle life curve of the electrolyte prepared in Example 9 in a Gr / LCO button cell. Fig.13 (b) is a charge-discharge curve of the electrolyte prepared in Example 9 in a Gr / LCO button cell; Fig.14(a) is a cycle life curve of the electrolyte prepared in Example 10 in a Gr / LCO button cell. Fig.14 (b) is a charge-discharge curve of the electrolyte prepared in Example 10 in a Gr / LCO button cell; Fig.15 (a) is a cycle life curve of the electrolyte prepared in Example 11 in a Gr / LCO button cell, Fig.15 (b) is a charge-discharge curve of the electrolyte prepared in Example 11 in a Gr / LCO button cell; Fig.16 (a) is a cycle life curve of the electrolyte prepared in Example 12 in a Gr / LCO button cell. Fig.16 (b) is a charge-discharge curve of the electrolyte prepared in Example 12 in a Gr / LCO button cell; Fig.17 (a) is a cycle life curve of the electrolyte prepared in Example 13 in a Gr / LCO button cell. Fig.17 (b) is a charge-discharge curve of the electrolyte prepared in Example 13 in a Gr / LCO button cell; Fig.18 (a) is a cycle life curve of the electrolyte prepared in Example 14 in a Gr / LCO button cell. Fig.18 (b) is a charge-discharge curve of the electrolyte prepared in Example 14 in a Gr / LCO button cell; Fig.19 (a) is a cycle life curve of the electrolyte prepared in Example 15 in a Gr / LCO button cell, Fig.19 (b) is a charge-discharge curve of the electrolyte prepared in Example 15 in a Gr / LCO button cell; Fig. 20 (a) is a cycle life curve of the electrolyte prepared in Example 16 in a Gr / LCO button cell. Fig. 20 (b) is a charge-discharge curve of the electrolyte prepared in Example 16 in a Gr / LCO button cell; Fig.21 (a) is a cycle life curve of the electrolyte prepared in Example 17 in a Gr / LCO button cell. Fig.21 (b) is a charge-discharge curve of the electrolyte prepared in Example 17 in a Gr / LCO button cell; Fig. 22 (a) is a cycle life curve of the electrolyte prepared in Example 18 in a Gr / LCO button cell. Fig. 22 (b) is a charge and discharge curve of the electrolyte prepared in Example 18 in a Gr / LCO button cell. DETAILED DESCRIPTION

[0023] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0024] In the following embodiments, the preparation method of the lithium ion battery includes: (1) Preparation of positive electrode sheets: Lithium cobalt oxide (LiCoO2, LCO), binder polyvinylidene fluoride (PVDF) and conductive carbon black are added to an appropriate amount of N-methylpyrrolidone (NMP) in a mass ratio of 90:5:5, mixed evenly to obtain a slurry, which is then evenly coated on an aluminum foil current collector, dried at 110°C, and then cut to obtain the desired positive electrode sheets.

[0025] (2) Preparation of negative electrode sheets: Artificial graphite (Gr), binder polyacrylonitrile (LA133), and conductive carbon black are added to deionized water in a mass ratio of 93:5:2, mixed evenly to obtain a slurry, which is then evenly coated on a copper foil current collector, dried at 90°C, and then cut into pieces to obtain the desired negative electrode sheets.

[0026] (3) Preparation of electrolyte: In a glove box filled with inert gas (O2<0.1ppm, H2O<0.1ppm), organic solvents were mixed according to a mass ratio, and then lithium salt was slowly added to the mixed solution to obtain a basic electrolyte. Additives in different amounts were added to the basic electrolyte to obtain electrolytes of the corresponding embodiments and comparative examples.

[0027] (4) Battery assembly: In a glove box (O2<0.1ppm, H2O<0.1ppm), assemble button cells in the order of positive electrode shell-positive electrode sheet-diaphragm-negative electrode sheet-stainless steel sheet-spring sheet-negative electrode shell, add an appropriate amount of electrolyte, and finally package to obtain the corresponding test battery.

[0028] (5) Battery test: The Gr||LCO (3.0V~4.55V) button cells assembled in the examples and comparative examples were activated for 2 cycles at room temperature (25°C) and 0.1C rate. The DC resistance (DCR) of the button cells was tested at 50% state of charge (SOC). Then, a long cycle test with a charge and discharge rate of 0.5C was performed, and the number of cycles corresponding to the decay of the cycle capacity retention rate of the button cells to 80% was recorded.

[0029] The following is an explanation of my own proposal based on specific cases.

[0030] Example 1

[0031] LiPF6 was slowly dissolved in EC, EMC and DEC with a mass ratio of 1:1:1, so that the concentration of LiPF6 was 1 mol / L, and a reference electrolyte was prepared; Add the functional additive to the reference electrolyte so that the functional additive accounts for 1% of the total mass of the electrolyte, mix evenly until completely dissolved, and obtain an electrolyte. The Chinese name of the added functional additive is m-fluorophenyl trifluoromethanesulfonate, and the structural formula is as follows: The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Figure 1 : After the above electrolyte was cycled for 284 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 10.2Ω.

[0032] Example 2

[0033] The configuration of this embodiment is the same as that of embodiment 1, except that the Chinese name of the functional additive is 2,4-difluorophenyl trifluoromethanesulfonate, and its structural formula is as follows: The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Figure 2 : After the above electrolyte was cycled for 288 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 11.5Ω.

[0034] Example 3

[0035] The configuration of this embodiment is the same as that of embodiment 1, except that the Chinese name of the functional additive is 4-(trifluoromethyl)phenyl trifluoromethanesulfonate, and its structural formula is as follows: The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Figure 3 : After the above electrolyte was cycled for 294 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 9.8Ω.

[0036] Example 4

[0037] The configuration of this embodiment is the same as that of embodiment 1, except that the Chinese name of the functional additive is pentafluorophenol trifluoromethanesulfonate, and its structural formula is as follows: The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Figure 4 : After the above electrolyte was cycled for 518 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 9.6Ω.

[0038] Example 5

[0039] The configuration of this embodiment is the same as that of embodiment 1, except that the Chinese name of the functional additive is 4-cyanophenyl trifluoromethanesulfonate, and its structural formula is as follows: The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Figure 5 : After the above electrolyte was cycled for 322 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 10.6Ω.

[0040] Example 6

[0041] The configuration of this embodiment is the same as that of embodiment 1, except that the Chinese name of the functional additive is 2-(trimethylsilyl)phenyl trifluoromethanesulfonate, and its structural formula is as follows: The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Figure 6 : After the above electrolyte was cycled for 335 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 11.4Ω.

[0042] Example 7

[0043] The configuration of this embodiment is the same as that of embodiment 1, except that the Chinese name of the functional additive is: 4-methyl-2-(trimethylsilyl)phenyl trifluoromethanesulfonate, and its structural formula is as follows: The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Figure 7 : After the above electrolyte was cycled for 450 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 8.6Ω.

[0044] Example 8

[0045] The configuration of this embodiment is the same as that of embodiment 1, except that the Chinese name of the functional additive is: 4,5-difluoro-2-(trimethylsilyl)phenyl trifluoromethanesulfonate, and its structural formula is as follows: The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Figure 8 : After the above electrolyte was cycled for 478 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 9.0Ω.

[0046] By comparing the above examples, it can be seen that the functional additives provided by the present invention can achieve good cycle performance and coulomb efficiency. However, under the same conditions, when the functional additives are pentafluorophenol trifluoromethanesulfonate (Example 4), 4-methyl-2-(trimethylsilyl)phenyl trifluoromethanesulfonate (Example 7), and 4,5-difluoro-2-(trimethylsilyl)phenyl trifluoromethanesulfonate (Example 8), the cycle number can reach more than 450, and the DC impedance of the battery at 25°C is controlled at around 9.0Ω. At this time, the cycle performance and coulomb efficiency of the battery are the best.

[0047] Comparative Example 1

[0048] The configuration of this comparative example is the same as that of Example 1, except that no functional additive is added, that is, the reference electrolyte is used as the electrolyte.

[0049] The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Fig. 9 : After the above electrolyte was cycled for 167 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 15.3Ω.

[0050] By comparing Examples 1 to 8 with Comparative Example 1, it can be seen that under the same conditions, the number of cycles of the battery obtained in Comparative Example 1 without adding functional additives is only 167, and the DC impedance of the battery at 25°C is 15.3Ω; while the number of cycles of the battery obtained in the solution with functional additives is basically maintained at around 300 or above, and the DC impedance of the battery at 25°C is about 10.0Ω. The electrolyte provided in the present application achieves better cycle performance, higher coulomb efficiency and smaller interface impedance, which is mainly because the electrolyte provided in the present application can form a protective interface film on the surface of the positive electrode, significantly improving the stability of the electrode-electrolyte interface, thereby reducing the consumption, decomposition and damage to the positive electrode structure of the electrolyte during the cycle, effectively improving the cycle performance and coulomb efficiency of the lithium-ion battery, and specifically reflected in the number of cycles and DC impedance.

[0051] Comparative Example 2

[0052] The configuration of this embodiment is the same as that of embodiment 1, except that the functional additive is pentafluorophenol trifluoromethanesulfonate, and its content accounts for 0.05% of the total mass of the electrolyte.

[0053] The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Fig.10 : After the above electrolyte was cycled for 168 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 15.0Ω.

[0054] By comparing Comparative Example 1, Comparative Example 2 and Example 4, it can be seen that when the amount of the functional additive added is less than 0.1 wt %, the improvement effect is not obvious.

[0055] Comparative Example 3

[0056] The configuration of this embodiment is the same as that of embodiment 1, except that the functional additive is pentafluorophenol trifluoromethanesulfonate, and its content accounts for 3.5% of the total mass of the electrolyte.

[0057] The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Fig.11 : After the above electrolyte was cycled for 344 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 12.4Ω.

[0058] By comparing Comparative Example 1, Comparative Example 3 and Example 4, it can be seen that when the amount of functional additives added is higher than 3wt%, the benefit to the battery cycle life deteriorates. This may be because the excessively high content of functional additives leads to a thicker CEI film and a higher impedance, which in turn leads to poor cycle performance.

[0059] Comparative Example 4

[0060] The configuration of this embodiment is the same as that of Embodiment 1, except that the electrolyte does not contain any functional additives but only contains sulfur-based additives: LiPF6 is slowly dissolved in EC, EMC and DEC in a mass ratio of 1:1:1, and then the sulfur-based additive vinyl sulfate is slowly added to make the concentration of LiPF6 1 mol / L, and vinyl sulfate accounts for 2% of the total mass of the electrolyte, and the electrolyte is stirred until it is completely dissolved.

[0061] The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Fig.12 : After the above electrolyte was cycled for 231 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 14.0Ω.

[0062] Comparison of Comparative Example 4 with Comparative Example 1 and Example 4 shows that: although Comparative Example 4 containing only sulfur-based additives can increase the number of cycles and reduce the DC impedance to a certain extent compared with Comparative Example 1 without any additives, its effect is far inferior to Example 4 containing functional additives. The addition of the functional additives provided in this case can significantly increase the number of cycles and reduce the DC impedance.

[0063] Taking Example 4 as an example, the dosage of the functional additive and the effect of the sulfur-based additive are verified, as shown in Examples 9 to 18.

[0064] Example 9

[0065] The configuration of this embodiment is the same as that of embodiment 1, except that the functional additive is pentafluorophenol trifluoromethanesulfonate, and its content accounts for 0.1% of the total mass of the electrolyte.

[0066] The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Fig.13 : After the above electrolyte was cycled for 216 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 13.8Ω.

[0067] Example 10

[0068] The configuration of this embodiment is the same as that of embodiment 1, except that the functional additive is pentafluorophenol trifluoromethanesulfonate, and its content accounts for 0.5% of the total mass of the electrolyte.

[0069] The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Fig.14 : After the above electrolyte was cycled for 380 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 11.5Ω.

[0070] Embodiment 11

[0071] The configuration of this embodiment is the same as that of embodiment 1, except that the functional additive is pentafluorophenol trifluoromethanesulfonate, and its content accounts for 2% of the total mass of the electrolyte.

[0072] The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Fig.15 : After the above electrolyte was cycled for 516 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 9.9Ω.

[0073] Example 12

[0074] The configuration of this embodiment is the same as that of embodiment 1, except that the functional additive is pentafluorophenol trifluoromethanesulfonate, and its content accounts for 3% of the total mass of the electrolyte.

[0075] The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Fig.16 : After the above electrolyte was cycled for 440 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 10.6Ω.

[0076] Example 13

[0077] The configuration of this embodiment is the same as that of embodiment 1, except that the functional additive is pentafluorophenol trifluoromethanesulfonate, and its content accounts for 4% of the total mass of the electrolyte.

[0078] The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Fig.17 : After the above electrolyte was cycled for 307 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 13.5Ω.

[0079] By comparing Comparative Example 3, Example 4 and Example 13, it can be seen that under the same conditions, when the amount of functional additive added is 3.5% and 4%, there is no significant improvement in the number of cycles and DC impedance. It can be seen that when the content of functional additives is >3%, the increase of functional additives will lead to a worsening of the benefits of battery cycle life. This may be because when the content of additives is too high, the interface film formed on the positive electrode side is too thick and the interface impedance is too large. When the amount of functional additives added is controlled at 1-3%, the electrolyte cycle number and DC impedance performance are optimal.

[0080] Embodiment 14

[0081] The configuration of this embodiment is the same as that of Embodiment 1, except that a sulfur-based additive is further added to the electrolyte: LiPF6 is slowly dissolved in EC, EMC and DEC in a mass ratio of 1:1:1, and then the functional additive pentafluorophenol trifluoromethanesulfonate and the sulfur-based additive vinyl sulfate are slowly added to make the concentration of LiPF6 1 mol / L, the functional additive accounts for 1% of the total mass of the electrolyte, and the vinyl sulfate accounts for 2% of the total mass of the electrolyte, and the electrolyte is stirred until it is completely dissolved.

[0082] The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Fig.18 : After the above electrolyte was cycled for 573 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 8.9Ω.

[0083] Embodiment 15

[0084] The configuration of this embodiment is the same as that of Embodiment 1, except that a sulfur-based additive is further added to the electrolyte: LiPF6 is slowly dissolved in EC, EMC and DEC in a mass ratio of 1:1:1, and then the functional additive pentafluorophenol trifluoromethanesulfonate and the sulfur-based additive 1,3-propane sultone are slowly added to make the concentration of LiPF6 1 mol / L, the functional additive accounts for 1% of the total mass of the electrolyte, and 1,3-propane sultone accounts for 2% of the total mass of the electrolyte, and the electrolyte is stirred until it is completely dissolved.

[0085] The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Fig.19 : After the above electrolyte was cycled for 527 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 9.2Ω.

[0086] Comparing Example 4 with Example 14 and Example 15, it can be seen that compared with Example 4 containing only functional additives, Examples 14 and 15 containing both functional additives and sulfur-based additives can significantly increase the number of cycles, directly increasing the number of cycles to more than 500. It can be seen that the combined use of functional additives and sulfur-based additives effectively protects the positive and negative electrode interfaces, thereby further improving the coulombic efficiency and cycle stability of the full battery; relatively speaking, the improvement effect of 1,3-propane sultone on cycle stability is lower than that of vinyl sulfate. However, the combined use of functional additives and sulfur-based additives has no significant effect on reducing DC impedance, and both remain near 9.0Ω regardless of the combined use or the use of functional additives alone.

[0087] Example 16

[0088] The configuration of this embodiment is the same as that of Embodiment 1, except that a sulfur-based additive is further added to the electrolyte: LiPF6 is slowly dissolved in EC, EMC and DEC in a mass ratio of 1:1:1, and then the functional additive pentafluorophenol trifluoromethanesulfonate and the sulfur-based additive vinyl sulfate are slowly added to make the concentration of LiPF6 1 mol / L, the functional additive accounts for 1% of the total mass of the electrolyte, and the vinyl sulfate accounts for 3% of the total mass of the electrolyte, and the electrolyte is stirred until it is completely dissolved.

[0089] The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Fig. 20 : After the above electrolyte was cycled for 535 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 9.3Ω.

[0090] Embodiment 17

[0091] The configuration of this embodiment is the same as that of Embodiment 1, except that a sulfur-based additive is further added to the electrolyte: LiPF6 is slowly dissolved in EC, EMC and DEC in a mass ratio of 1:1:1, and then the functional additive pentafluorophenol trifluoromethanesulfonate and the sulfur-based additive vinyl sulfate are slowly added to make the concentration of LiPF6 1 mol / L, the functional additive accounts for 1% of the total mass of the electrolyte, and the vinyl sulfate accounts for 4% of the total mass of the electrolyte, and the electrolyte is stirred until it is completely dissolved.

[0092] The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Fig.21 : After the above electrolyte was cycled for 396 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 12.6Ω.

[0093] Embodiment 18

[0094] The configuration of this embodiment is the same as that of Embodiment 1, except that a sulfur-based additive is further added to the electrolyte: LiPF6 is slowly dissolved in EC, EMC and DEC in a mass ratio of 1:1:1, and then the functional additive pentafluorophenol trifluoromethanesulfonate and the sulfur-based additive vinyl sulfate are slowly added to make the concentration of LiPF6 1 mol / L, the functional additive accounts for 2% of the total mass of the electrolyte, and the vinyl sulfate accounts for 4% of the total mass of the electrolyte, and the electrolyte is stirred until it is completely dissolved.

[0095] The obtained electrolyte was prepared into a battery and its performance was tested. The results are shown in Fig. 22 : After the above electrolyte was cycled for 228 cycles at a charge cut-off voltage of 4.55 V, the capacity retention rate decayed to 80%. The DC impedance of the battery at 25°C was 17.2Ω.

[0096] By comparing Example 4 with Examples 14 to 18, it can be seen that although Example 18 also adopts a combination mode of functional additives and sulfur-based additives, since the total amount of functional additives and sulfur-based additives added x+y>5, the interface film formed on the positive electrode surface is too thick, resulting in excessive battery impedance, making its DC impedance reach 17.2Ω, which affects the transmission of lithium ions and further affects the cycle performance of the battery, reducing its cycle number to around 200.

[0097] From the above we can see that: 1) When the electrolyte of the present application uses a compound containing a phenyl substituent of trifluoromethyl sulfonate as a functional additive, the cycle performance and coulombic efficiency of the battery can be effectively improved, especially when the mass percentage of the functional additive in the electrolyte is controlled at 1-3%, and in the structural formula thereof, one or more of R1-R5 are selected from hydrogen atoms (such as in Examples 1-3, 5-8), fluorine atoms (such as in Examples 1, 2, 4, 8), trimethylsilyl (such as R1 in Examples 6 and 7), cyano (R3 in Example 5 is cyano), C 1~10 Alkyl (such as R3 in Example 7 is methyl) and halogen substituted C 1~10 The best functional additive is any one of the alkyl groups (such as R3 in Example 3 is trifluoromethyl), and pentafluorophenol trifluoromethanesulfonate, 4-methyl-2-(trimethylsilyl)phenyl trifluoromethanesulfonate, and 4,5-difluoro-2-(trimethylsilyl)phenyl trifluoromethanesulfonate.

[0098] 2) Compared with the use of sulfur additives alone, the electrolyte obtained when the functional additives are used alone has a much better improvement effect on the battery cycle performance and coulomb efficiency than the use of sulfur additives alone. Compared with the use of functional additives alone, the electrolyte combined with sulfur additives can more significantly improve the cycle performance and coulomb efficiency. The total addition amount x+y of the two in the electrolyte is appropriately controlled below 1~3%. When it exceeds 4%, the cycle performance will decrease; when it exceeds 5%, the number of cycles will be significantly reduced. The sulfur additive used in combination with the functional additive is preferably selected from any one of vinyl sulfate (DTD), 1,3-propane sultone (PS), propenyl-1,3-sultone (PES), ethylene sulfite (ES), 4-propyl vinyl sulfate (PDTD), methylene disulfonate (MMDS), and methyl vinyl sulfone (MVS). Among them, vinyl sulfate (DTD) and 1,3-propane sultone (PS) have the best synergistic effect. The total content of additives x+y in the electrolyte is appropriately controlled at 0.1-5%, and preferably 1-4%. In this value range, the number of cycles is maintained above 350, and the DC impedance is maintained near 10Ω. In particular, when the functional additive is pentafluorophenol trifluoromethanesulfonate, when 1%≤x+y≤4%, it can basically ensure that the number of cycles is above 500, and the DC impedance is maintained near 9.0Ω.

Claims

1. An electrolyte, characterized in that: The invention comprises an electrolyte salt, an organic solvent and a functional additive, wherein the mass percentage of the functional additive in the electrolyte is 0.1-3%, and the structure of the functional additive contains a phenyl substituent of trifluoromethyl sulfonate, and the structural formula thereof satisfies: , R1~R5 are each independently selected from hydrogen atom, C 1~10 Alkyl, substituted C 1~10 Any of an alkyl group, a fluorine atom, a trifluoromethyl group, a trimethylsilyl group, and a cyano group.

2. An electrolyte according to claim 1, characterized in that: The mass percentage of functional additives in the electrolyte is 1~3%.

3. An electrolyte according to claim 1, characterized in that: The functional additive is any one of the following structures: 。 4. An electrolyte according to claim 1, characterized in that: The electrolyte salt is a lithium salt or a sodium salt with a concentration of 0.1 to 3.0 mol / L.

5. An electrolyte according to claim 1, characterized in that: The organic solvent is one of carbonate ester and carboxylate ester or a mixture of both.

6. An electrolyte according to any one of claims 1 to 5, characterized in that: It also includes a sulfur additive, and the mass percentage y of the sulfur additive in the electrolyte and the mass percentage x of the functional additive in the electrolyte satisfy: 0.1%≤x+y≤5%, y≥0.

7. An electrolyte according to claim 6, characterized in that: The mass percentage y of the sulfur-based additive in the electrolyte and the mass percentage x of the functional additive in the electrolyte satisfy: 1%≤x+y≤4%.

8. An electrolyte according to claim 6, characterized in that: The sulfur-based additive is selected from at least one of vinyl sulfate, 1,3-propane sultone, propenyl-1,3-sultone, ethylene sulfite, 4-propyl vinyl sulfate, methylene methane disulfonate, and methyl vinyl sulfone.

9. A battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator arranged between the positive electrode and the negative electrode, and the electrolyte according to claim 1, wherein the functional additive in the electrolyte forms a film at the positive electrode to inhibit the side reaction of the electrolyte at the positive electrode interface.

10. A battery according to claim 9, characterized in that: The electrolyte contains a sulfur-based additive, which forms a film on the negative electrode to inhibit side reactions of the electrolyte at the negative electrode interface.

Citation Information

Patent Citations

  • Nonaqueous electrolyte solution, electricity storage device using same, and trifluoromethylbenzene compound

    CN103493277A

  • Lithium ion battery and electrolyte thereof

    CN105161753A

  • Fluorine-containing sulfonate electrolyte additive, electrolyte containing additive and lithium ion battery

    CN112054241A

  • Lithium ion battery non-aqueous electrolyte and lithium ion battery

    CN112310475A

  • Electrolyte, secondary battery and electric equipment

    CN115411363A

Cited By

  • Preparation method and application of water-resistant electrolyte for sodium-ion battery

    CN119920981A